Noninvasive Measurement of Electrical Events Associated with a Single Chlorovirus Infection of a Microalgal Cell - Lee, Seung Woo; Lee, Eun-Hee; Thiel, Gerhard; Van Etten, James L.; Saraf, Ravi F. (AMER CHEMICAL SOC, 2016)
Chlorovirus Paramecium bursaria chlorella virus 1 (PBCV-1) contains a viral-encoded K+ channel imbedded in its internal membrane, which triggers host plasma membrane depolarization during virus infection. This early stage of infection was monitored at high resolution by recording the cell membrane depolarization of a single Chlorella cell during infection by a single PBCV-1 particle. The measurement was achieved by depositing the cells onto a network of one-dimensional necklaces of Au nanoparticles, which spanned two electrodes 70 mu m apart. The nanoparticle necklace array has been shown to behave as a single-electron device at room temperature. The resulting electrochemical field-effect transistor (eFET) was gated by the cell membrane potential, which allowed a quantitative measurement of the electrophysiological changes across the rigid cell wall of the microalgae due to a single viral attack at high sensitivity. The single viral infection signature was quantitatively confirmed by coupling the eFET measurement with a method in which a single viral particle was delivered for infection by a scanning probe microscope cantilever.